2022
DOI: 10.1371/journal.pone.0264839
|View full text |Cite
|
Sign up to set email alerts
|

Performance of COVID-19 case-based surveillance system in FCT, Nigeria, March 2020 –January 2021

Abstract: Introduction The emergence of novel SARS-CoV-2 has caused a pandemic of Coronavirus Disease 19 (COVID-19) which has spread exponentially worldwide. A robust surveillance system is essential for correct estimation of the disease burden and containment of the pandemic. We evaluated the performance of COVID-19 case-based surveillance system in FCT, Nigeria and assessed its key attributes. Methods We used a cross-sectional study design, comprising a survey, key informant interview, record review and secondary da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Figure 3 provides case examples of EVD-related countries’ policy learning. Nigeria and Liberia’s COVID-19 national response in 2020 were notably organized and effective at mitigating the first waves often attributed to their EVD-related policy improvements [ 21 , 22 , 55 – 58 ]. One critical factor repeatedly noted is how many of these nations employed a key lesson learnt in the Ebola crisis- the need to identify culturally and contextually appropriate solutions [ 13 , 21 , 49 , 51 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 provides case examples of EVD-related countries’ policy learning. Nigeria and Liberia’s COVID-19 national response in 2020 were notably organized and effective at mitigating the first waves often attributed to their EVD-related policy improvements [ 21 , 22 , 55 – 58 ]. One critical factor repeatedly noted is how many of these nations employed a key lesson learnt in the Ebola crisis- the need to identify culturally and contextually appropriate solutions [ 13 , 21 , 49 , 51 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The World Bank’s International Development Association-supported Regional Disease Surveillance Systems Enhancement (REDISSE) Program was launched in 2016 to support 2014-16 EVD-affected nations and non-affected nations (Benin, Burkina Faso, Cabo Verde, Cote d’Ivoire, The Gambia, Ghana, Guinea-Bissau, Mali, Mauritania, Niger, Nigeria, Senegal, Togo) to incorporate EVD-related policies to better guard against future epidemics. To varying levels of degree, these countries included REDISSE health reforms to combat COVID, including rapid laboratory testing, forming a technical preparedness working group, and activating Incident Action Plans transnationally [ 22 , 66 – 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of Nigeria's COVID-19 testing system as well as the acceptance of the COVID-19 vaccines depends on several factors which included the willingness of citizens to be tested, proximity to the testing center, the individual's level of education, preexisting health conditions, knowledge of COVID-19 symptoms, and previous healthcare experience [5,[22][23][24][25]. In addition, risk communication and community engagement strategies have in uenced healthcare seeking behavior of Nigerians, speci cally during the COVID-19 pandemic [26].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the sample size of the study, Fisher's formula [15] for estimating single proportions and estimation for minimum sample size was applied, and the estimated sample size was 73. Fisher's formula: n=Z 2 P (1−P)/d 2 ; where: n=sample size, Z=standard deviation for a 95% confidence level (Z=1.96), and p=prevalence of the attribute which was obtained from Umeozuru, et al [16] where 5% of health care workers reported at least one suspected COVID-19 case on an e-IDSR platform in FCT, Nigeria; while d = acceptable difference (if 5%, d=0.05); q=1-p.…”
Section: Study Design Sample Size Estimation and Sampling Methodsmentioning
confidence: 99%